PENGARUH MODEL PEMBELAJARAN SELF DIRECTED LEARNING TERHADAP AKTIVITAS DAN HASIL BELAJAR IPA KELAS IV SEKOLAH DASAR - Anjun; Khoimatun; Tobroni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is entitled The Influence of the Self Directed Learning Model on Activities and Learning Outcomes in Class IV Elementary School Science. This research was motivated by the low level of student activity and learning outcomes. This research aims to determine the effect of the self-directed learning model on science learning activities and outcomes in grade IV elementary school. This research is a type of quasi-experimental research. The research design used was a pretest-posttest only control group design, with the research sample consisting of two classes, namely class IVA as an experimental class with a total of 38 students and class IVB as a control class with a total of 34 students. This research uses questionnaire and test data collection, all of this data is to determine the effectiveness of the influence of the self-directed learning model. Based on the data analyzed, it shows that for learning activities using the independent sample t test the results obtained a sig value (2-tailed) 0.030<0.05 which shows that there is a difference in the results of the questionnaire in the experimental class and the control class, while the learning results obtained the results sig (2-tailed) 0.013<0.05 which shows that there is a difference in the learning outcomes of experimental class students with the control class, and to increase learning outcomes using the n-gain test which shows that the average score of the experimental class pretest 74.02 posttest 80.13 and n-gain value 0.83 with high criteria while the average value of the pretest control class was 75.11 posttest 76.44 and n-gain value 0.65 with medium criteria. This shows that the self-directed learning model can improve student learning outcomes.